Probiotics in the Prevention and Treatment of Periodontal Diseases: A Systematic Review - Nishath Sayed Abdul; Lara Ghassan Odeh; Asma Awadh Alenazi; Jumana Abdullah Alzahrani; Aldanah Tawfiq Almutib; Cristalle Soman (Journal of Pharmacy and Bioallied Sciences)
Introduction: Periodontal diseases (PDs) pose a significant challenge to dental health, leading to a growing interest in probiotics as potential therapeutic and prophylactic agents. Literature evidence has shown conflicting results on the use of probiotics in the management of PDs. Hence, this systematic review was performed to explore the effectiveness of probiotics in both the prevention and treatment of PDs by synthesizing data from relevant studies. Methodology: Various databases were searched using appropriate MeSH keywords as per the PRISMA protocol. Studies were included only if they met certain criteria. Two reviewers independently extracted data variables from the included literature. The risk of bias 2.0 tool was employed to assess the methodological quality of the included studies. Results: In total, 21 studies were considered eligible and included in the review. It was observed that 17 studies reported a statistically significant improvement in both periodontitis and gingivitis among the probiotic group compared to control cohorts. The synthesized evidence from the review suggests that probiotics play a favourable role in both the prevention and treatment of PDs. Conclusion: It also supports the incorporation of probiotics as a potential adjunctive therapy in PD management. However, further research is warranted to explore the specific probiotic strains, dosages, and treatment durations for optimized outcomes.